Interdisciplinary study of alexithymia - E.A. Gorobets; R.G. Esin; Yu.A. Volskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
In modern science, alexithymia is defined as the specific cognitive status of a person who has marked difficulties in understanding and exteriorizing one's feelings, emotions, experiences, and impressions, as well as in separating them from bodily sensations and in perceiving the feelings and emotions of other people. Alexithymic disorders have been actively studied by doctors of various profiles, psychologists, neurophysiologists, and also – over the past decade – by linguists. This article discusses the features of alexithymia in its connection with the problems of clinical practice, the manifestations of alexithymia in various fields, and the specifics of its interdisciplinary study. The relationship of alexithymia with the risk and more severe course of various somatic diseases is analyzed. Particular attention is paid to the difficulties of diagnostic procedures in the presence of a high level of alexithymia in patients. Various classifications of alexithymia are considered. A review of modern neurostudies on alexithymia seeking to further explore it and identify optimal therapeutic strategies is provided.